2021
DOI: 10.3390/su13084421
|View full text |Cite
|
Sign up to set email alerts
|

Executives’ Environmental Awareness and Eco-Innovation: An Attention-Based View

Abstract: Eco-innovation is conducive to reducing the costs and impacts on the environment. Meanwhile, executives play an important role in the whole process of enterprise innovation. However, it is unclear whether and to what extent executives’ environmental awareness (EA) affects eco-innovation (EI). Based on the attention-based view, this study discussed the mediating effect of resource flexibility (RF) on the impact of EA on EI and explored the moderating effect of unabsorbed slack resources (USRs). Using surveys co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 82 publications
3
14
0
Order By: Relevance
“…Fourth, our results also support the hypothesis that GIA mediates the influence of TMT's response on both green innovation performance and economic performance. This finding contributes to and advances the literature (Ar, 2012;Kumar et al, 2012;Ma et al, 2021;Sun and Sun, 2021;Ye et al, 2013) by showing that TMT's response plays a critical role in affecting GIA, which in turn predicts firm performance. EJIM 27,3…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Fourth, our results also support the hypothesis that GIA mediates the influence of TMT's response on both green innovation performance and economic performance. This finding contributes to and advances the literature (Ar, 2012;Kumar et al, 2012;Ma et al, 2021;Sun and Sun, 2021;Ye et al, 2013) by showing that TMT's response plays a critical role in affecting GIA, which in turn predicts firm performance. EJIM 27,3…”
Section: Discussionsupporting
confidence: 68%
“…However, argued that the vision of top executives for environmental sustainability is crucial to firms' successful implementation of green initiatives. Sun and Sun (2021) stated that TMT's environmental awareness affects eco-innovation (both management and product innovation), which improves competitiveness and sustainable management. In the same vein, Ma et al (2021) emphasized that TMTs concerned about environmental issues will tend to regard green innovation for the purpose of protecting the environment as a development opportunity, linking it with the green brand image and environmental friendliness, to grasp the potential opportunities and economic returns brought about by the green innovation strategy.…”
Section: 58mentioning
confidence: 99%
“…This includes: industry characteristics related to the typology of the organisations and the business sector (Cai and Li, 2018); external market orientation, in which the organisation emphasises the role it plays in identifying the needs and desires of consumers and creating products that satisfy them (Peris et al, 2020;Triguero et al, 2017); and the adoption of environmental systems that aim at the continuous improvement of a company's environmental performance (Brogi and Menichini, 2019;Tseng et al, 2021). Environmental regulation (Doran and Ryan, 2012); market pressures arising from society's increased environmental awareness, particularly through the realisation of how our actions cause short-, medium-and long-term impacts (Sumrin et al, 2021;Sun and Sun, 2021); and collaborative partnerships in which we highlight initiatives carried out in partnerships between several organisations and civil society (Araújo and Franco, 2021;Sanchez-Henriquez and Pavez, 2021) are all contributing elements that stimulate and promote eco-innovation. The knowledge about the facilitators of ecoinnovation adoption conducted to the proposal of the following hypotheses:…”
Section: Eco-innovationmentioning
confidence: 99%
“…Among CS research, by a comprehensive investigation of 1249 works within the literature from 2000 to 2020, the study [69] concluded that top managers are the great driving force and pioneers of corporations engaged in responsible social and environmental practice. Previous studies have shown that leaders with stronger green perceptions are more likely to promote green behavior change in corporations [69][70][71]. The personality, values, achievement motivation, or power desire of executives can influence their decision on CS development [72,73], but attitudes or intentions to environmental sustainability play vital roles [71,72,74,75].…”
Section: Internal Perception and Corporate Behaviormentioning
confidence: 99%
“…Previous studies have shown that leaders with stronger green perceptions are more likely to promote green behavior change in corporations [69][70][71]. The personality, values, achievement motivation, or power desire of executives can influence their decision on CS development [72,73], but attitudes or intentions to environmental sustainability play vital roles [71,72,74,75].…”
Section: Internal Perception and Corporate Behaviormentioning
confidence: 99%